The effect of Apolipoprotein E4 on cognitive function in Parkinson’s disease: A structural MRI study in the PPMI cohort - Angenelle Eve Rosal; Edgardo Torres-Carmona; Sarah L. Martin; Isabelle Boileau; Ariel Graff-Guerrero; Antonio P. Strafella (PLoS ONE, 2026)
Background Cognitive impairment is a common non-motor symptom of Parkinson’s disease (PD), yet its underlying mechanisms remain poorly understood. Apolipoprotein E4 (APOE4) , a genetic risk factor of Alzheimer’s Disease, has been associated with PD-related cognitive impairment. However, findings are inconsistent, highlighting the need for further investigation. Neuroimaging studies have found gray matter abnormalities, mainly reductions in gray matter volume (GMV) and cortical thickness (CTh), in both cognitively impaired PD patients and APOE4 carriers. Yet, APOE4’s role in these structural changes and their cognitive impact in PD is underexplored. Aim This study aimed to determine whether APOE4 influences early structural brain differences in terms of GMV and CTh in PD prior to the emergence of cognitive dysfunction. Methods A total of 51 PD APOE4 carriers and 120 non-carriers who were cognitively unimpaired from the Parkinson’s Progression Markers Initiative (PPMI) database were included. T1-weighted MRI scans were used to calculate GMV and CTh in regions previously associated with PD-related cognitive impairment, including hippocampal subregions. Cognitive scores assessing global cognition and specific cognitive domains were used to examine associations between regions showing significant GMV or CTh group differences and cognitive performance. Results PD APOE4 carriers showed increased GMV in the left angular gyrus (AnG) and decreased GMV in the left nucleus accumbens (NAcc) compared to non-carriers, though neither survived multiple comparison correction. Left AnG GMV correlated with visuospatial function in both groups but did not remain significant after co-variate adjustment. Left NAcc GMV correlated with visuospatial function and working memory, but only in non-carriers even after co-variate adjustment. No group differences were observed in CTh measures and hippocampal subregion GMVs. Conclusions This study suggests that APOE4 may not influence cognitive function in PD by affecting GMV and CTh. However, longitudinal analyses must confirm these observations.